Cost-effectiveness of breast cancer screening in the National Breast and Cervical Cancer Early Detection Program - Rim, Sun Hee (Cancer Causes Control, 2019)
PURPOSE: To estimate the cost-effectiveness of breast cancer screening in the National Breast and Cervical Cancer Early Detection Program (NBCCEDP). METHODS: Using a modified CISNET breast cancer simulation model, we estimated outcomes for women aged 40–64 years associated with three scenarios: breast cancer screening within the NBCCEDP, screening in the absence of the NBCCEDP (no program), and no screening through any program. We report screening outcomes, cost, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratios (ICERs), and sensitivity analyses results. RESULTS: Compared with no program and no screening, the NBCCEDP lowers breast cancer mortality and improves QALYs, but raises health care costs. Base-case ICER for the program was $51,754/QALY versus no program and $50,223/QALY versus no screening. Probabilistic sensitivity analysis ICER for the program was $56,615/QALY [95% CI $24,069, $134,230/QALY] versus no program and $51,096/QALY gained [95% CI $26,423, $97,315/QALY] versus no screening. CONCLUSIONS: On average, breast cancer screening in the NBCCEDP was cost-effective compared with no program or no screening.